Equity asset valuation - Pinto, Jerald E. (Wiley, 2010)
A comprehensive look at the equity valuation process. With the Second Edition of Equity Asset Valuation, the distinguished team of Jerald Pinto, Elaine Henry, Thomas Robinson, and John Stowe, fully update information associated with this important discipline. Blending theory with practice, they detail the contemporary techniques used to determine the intrinsic value of an equity security, and show you how to successfully apply these techniques in both foreign and domestic markets. Unlike alternative works in this field, the Second Edition of Equity Asset Valuation clearly integrates finance an.
Revised edition of: Equity asset valuation / John D. Stowe [and others]. ©2007. - Includes bibliographical references (pages 413-418) and index. - Print version record and CIP data provided by publisher
Keywords: Investment analysis; Securities -- Valuation; Investments -- Valuation; Business enterprises -- Finance; Corporations -- Finance; Analyse financière; Investissements; Évaluation; BUSINESS & ECONOMICS; Investments & Securities; Stocks; Corporations; Finance; Business enterprises; Finance; Investments; Valuation; Securities; Valuation; Aktienanalyse; Aktienbewertung; Finanzanalyse; Portfolio Selection